Radiofrequency ablation of the sinuvertebral nerve for patients with discogenic low back pain following lumbar interbody fusion: a case series study - Wang, Lijie; Lu, Jie; Wang, Hongyan; He, Liangliang; Dou, Zhi; Zhao, Wenxing; Yang, Song; Liu, Dong; Yang, Liqiang (Frontiers in Neurology, 2025)
BackgroundThis study aimed to investigate the clinical value of radiofrequency ablation (RFA) of the sinuvertebral nerve (SVN) in the treatment of discogenic low back pain (DLBP) following lumbar interbody fusion.MethodsA total of 12 patients who underwent RFA of the SVN for DLBP after lumbar interbody fusion at the Pain Department of Xuanwu Hospital of Capital Medical University from February 2023 to August 2023 were included in this retrospective study.ResultsIn total, 12 patients with DLBP were included. The preoperative visual analog scale (VAS) score was 7.00(6.00, 7.75), while the postoperative VAS score at 1 day, 1 month, and 3 months was 1.00 (1.00, 1.00). This represented a statistically significant improvement compared to the preoperative period (all p = 0.002). The preoperative Pittsburgh Sleep Quality Index (PSQI) score was 14.42 ± 1.83, and the postoperative PSQI scores at 1 month and 3 months were 4.75 ± 1.06 and 2.17 ± 1.11, respectively (all p < 0.001).ConclusionRFA of the SVN provides satisfactory short-term clinical results in patients with DLBP following lumbar interbody fusion. It appears to be an effective treatment for patients with DLBP who have poor outcomes after open lumbar spine surgery.